Examining the Regulation of Connexin Expression Over the Course of the Estrous Cycle in Hippocampus and Spinal Cord - McLean, Ashleigh (Université d'Ottawa / University of Ottawa, 2013)
At the author’s request, the abstract has been removed due to the confidential nature of the thesis. It will be added once the embargo period has passed.
Keywords: Connexin; Gap junction; Hippocampus; Spinal cord; Estrous cycle